Don DeLillo’s White Noise: A Virilian Perspective - Pirnajmuddin, Hossein; Samani, Bahareh Bagherzadeh (Text Matters: A Journal of Literature, Theory and Culture, 2019)
Don DeLillo’s White Noise depicts a world of rapid techno-scientific and economical changes. Paul Virilio’s concepts of dromology and speed, as well as his notions of accident and technology, seem to be the most relevant in order to examine a novel centrally concerned with change, speed and technology. This article first offers an analysis of White Noise in the light of Virilio’s concept of integral accident in relation to the negative consequences brought about by industrial and technological progress. This is followed by a discussion of the relevance to the novel of Virilio’s theories about architecture and space. Finally, Virilio’s theories about the replacement of conventional war with pure and info wars are discussed in the context of the central event of the novel. Reading the American writer through the lens of the French theorist can shed light on the enduring relevance of both.